CaLD nurses transition to Australian tertiary hospital practice: Exposing the reality – A mixed methods study. Issue 4 (December 2015) - Holmes, Tina; Grech, Carol
Summary: Purpose: To investigate CaLD nurses' transition into the Australian workforce over the first 3 months of employment in tertiary hospitals. Design/method: Descriptive mixed method design, informed by the critical paradigm. Survey questionnaire and a focus group were used for data collection. Findings: The existence of a specific hospital orientation program was identified as a crucial factor in participants' successful transition. Discussion: Without a hospital based orientation program participants were more likely to experience failure to 'fit in'. This led to maladaptive behaviors where they did not actively seek, support or question practice through fear of drawing increased attention to themselves. Workplace implications: Results from the study raise serious implications for workplace safety of both the CaLD nurses and the patients they nurse. Government and health administrators need to invest in providing specific hospital orientation programs that support CaLD nurses' transition. The development of such hospital orientation programs need to be developed as to the specific learning requirements of these nurses or risk exposing them to maladaptive behaviors and potential adverse events as a result of this learned behavior.